Gubbubu

Visszahelyettesítve ezt az első egyenlet (*)-gal megjelölt formájába:
 
:: <math> m^{2} </math> &nbsp; <math> = </math> <math> b^{2}-x^{2} </math> <math> = </math> &nbsp; <math> b^{2} - \left( \frac{ -a^{2} + b^{2} + c^{2} }{2c} \right) ^{2} </math> &nbsp; <math> = </math> &nbsp; <math> b^{2} - \frac{ \left( -a^{2} + b^{2} + c^{2} \right) ^{2} }{ \left( 2c \right) ^{2} } </math> &nbsp; <math> = </math> &nbsp; <math> b^{2} - \frac{ \left( -a^{2} + b^{2} + c^{2} \right) ^{2} }{ 4c^{2} } </math> &nbsp; <math> = </math> <br> <math> = </math> &nbsp; <math> \frac { 2c4c^{2} \cdot b^{2} } {2c 4c^{2} } - \frac{ \left( -a^{2} + b^{2} + c^{2} \right) ^{2} } {2c 4c^{2} } </math> &nbsp; <math> = </math> &nbsp; <math> \frac { 4b^{2} c^{2} - \left( -a^{2}+b^{2}+c^{2} \right) ^{2} } { 4c^{2} } </math>